La stabilité des prix des ressources non renouvelables - McRae, James (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractOne particular problem with the competitive solution to resource pricing is the potential for resource price instability. Using monthly data on prices for five different minerals the author examines, with the help of statistical techniques, the behaviour of prices over the years 1922-1974. He finds that fears of potential resource price instability have been overstated. Due either to the capitalization reactions of resource owners, or to the fact that resource markets are characterized by a monopolized industrial structure, real resource prices appear to show remarkable stability.